#### Answer

$\frac{2}{3x-1}$+$\frac{3}{3x-1}$=$\frac{5}{3x-1}$

#### Work Step by Step

$\frac{2}{3x-1}$+$\frac{3}{3x-1}$=$\frac{5}{3x-1}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{2}{3x-1}$+$\frac{3}{3x-1}$=$\frac{5}{3x-1}$

$\frac{2}{3x-1}$+$\frac{3}{3x-1}$=$\frac{5}{3x-1}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.